Price tag of glaucoma care is minor compared with the total direct and indirect costs of glaucoma: Results from nationwide survey and register data. - Petri K M Purola; Joonas Taipale; Saku Väätäinen; Mika Harju; Seppo V P Koskinen; Hannu M T Uusitalo (PLoS ONE)
Background The estimations of the economic burden of glaucoma have focused on comparing different treatment modalities; hence, the total direct and indirect costs of glaucoma at population level are not well known. Objective To estimate the direct and indirect costs of glaucoma and its treatment in Finland. Methods Economic and glaucoma data were collected from the cross-sectional nationwide Health 2000 health examination survey linked to multiple national registers, which allowed a 13-year follow-up between 1999-2011 among survey participants. Direct costs covered eye- and non-eye-related hospitalizations and outpatient visits, outpatient health care services, and travel costs among participants aged 30 years or older, adjusted for age and sex. Indirect costs covered premature retirement and productivity losses among participants aged 30-64 years. Glaucoma patients (n = 192) were compared with non-glaucomatous population (n = 6,952). Results The annual additional total direct costs were EUR 2,660/glaucoma patient, EUR 1,769/glaucoma patient with medication, and EUR 3,979/operated glaucoma patient compared with persons without glaucoma. The respective additional total indirect costs were EUR 4,288, EUR 3,246, and EUR 12,902 per year. In total, the additional annual direct and indirect expenditures associated with glaucoma in Finland were EUR 202 million (0.86% of total expenditures of health care) and EUR 71 million (0.03% of the Finnish gross domestic product) arising mainly from non-eye-related hospitalizations and productivity losses, respectively. Conclusion Glaucoma is associated with an increased health care consumption mainly due to non-eye-related health care, which can be explained by the vision loss as well as increased number of co-morbidities among glaucoma patients. Therefore, glaucoma constitutes a major economic burden for the health care system and society, highlighting the importance of early glaucoma interventions. The difference in direct and indirect costs between glaucoma treatment groups is explained by the uneven distribution of co-morbidities.